2000
DOI: 10.1542/peds.105.6.e85
|View full text |Cite
|
Sign up to set email alerts
|

Georgia's Breastfeeding Promotion Program for Low-Income Women

Abstract: ABSTRACT. Objective. Beginning in 1990, Georgia's Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) initiated 5 new strategies to promote breastfeeding among its pregnant and postpartum clients. These strategies were implemented in 1991, each to be provided as an addition to its standard program of counseling on breastfeeding and distributing appropriate literature: 1) enhanced breastfeeding education, 2) breast pump loans, 3) hospital-based programs, 4) peer counseling, and 5) comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 24 publications
1
65
0
Order By: Relevance
“…Studies of WIC groups suggest that participants are aware of the health benefits of breast-feeding for their infants, and that structural barriers such as return to work are less of a problem than attitudinal barriers, including embarrassment about public feeding, the perception of breast-feeding as limiting or inconvenient, and fears of inadequate supply (38) . Such attitudes are amenable to intervention and education, and WIC Programmes designed to educate participants and provide peer-counselling support services have shown that they can positively impact breast-feeding in this population (39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of WIC groups suggest that participants are aware of the health benefits of breast-feeding for their infants, and that structural barriers such as return to work are less of a problem than attitudinal barriers, including embarrassment about public feeding, the perception of breast-feeding as limiting or inconvenient, and fears of inadequate supply (38) . Such attitudes are amenable to intervention and education, and WIC Programmes designed to educate participants and provide peer-counselling support services have shown that they can positively impact breast-feeding in this population (39)(40)(41) .…”
Section: Discussionmentioning
confidence: 99%
“…This makes direct comparisons of breastfeeding rates between studies problematic; this is especially true for the one study based on data from the 1990s. 56 The breastfeeding initiation rates for African American and AI/AN mothers remain significantly below the Healthy People 2020 goal, as does breastfeeding at 6 months for all groups.…”
Section: Limitationsmentioning
confidence: 99%
“…Two studies 56,57 were identified evaluating the effectiveness of enhanced breastfeeding programs. Supporting the findings of Chapman and Pérez-Escamilla, 22 results from one study 56 demonstrated that enhanced hospital practices and WIC-based services can have a significant impact on breastfeeding initiation rates.…”
Section: Enhanced Breastfeeding Programsmentioning
confidence: 99%
“…These benefits include protection for the infant from acute infections and chronic digestive diseases, and for the mother protection from ovarian and breast cancer (American Academy of Pediatrics, 1997; US Department of Health and Human Services, 2000). WIC programs that educate participants and provide peer-counseling support services can positively impact breastfeeding in this population (Ahluwalia et al, 2000;Finch and Daniel, 2002;Gross et al, 2009) and the new WIC food package design, effective October 1, 2009, is also an important breastfeeding promotion effort (Holmes et al, 2009;Institute of Medicine, 2005b). Given that up to half of all infants in the US participate in WIC (Ryan and Zhou, 2006), encouraging breastfeeding in this population could benefit the overall health of a substantial proportion of American women and children.…”
Section: Discussionmentioning
confidence: 99%